Diplomasi Lingkungan Selandia Baru dalam Menjadikan Laut Ross Antarctica sebagai Marine Protected Area melalui CCAMLR - Sholihat, Afifah Puti; Fasisaka, Idin; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT The exploitation of the Ross Sea impacted New Zealand directly. Ross Sea, the last ocean, in the Antarctic Continent is located not far from New Zealand. In establishing the Ross Sea as a Marine Protected Area (MPA), New Zealand practiced environmental diplomacy that is carried through the Commission for the Conservation of the Antarctic Marine Living Resources (CCAMLR). This study analyzes the stages of New Zealand's environmental diplomacy using a convention-protocol approach. The concepts that are used in this study are environmental diplomacy and convention-protocol approach. New Zealand went through various obstacles in convincing CCAMLR member states in ensuring the importance of the protection of the Ross Sea. Member states interest in fishing industries has been a huge challenge in reaching the consensus towards the Ross Sea MPA proposal. Research data is obtained from various sources such as books, journals, scientific research, and reports relating to this study. Keyword: New Zealand, Environmental Diplomacy, Ross Sea Antarctica, Convention-Protocol Approach.